Google hacking for penetration testers - Long, Johnny; Gardner, Bill; Brown, Justin (Waltham, MA : Elsevier Ltd., 2016)
"Google is the most popular search engine ever created, but Google's search capabilities are so powerful, they sometimes discover content that no one ever intended to be publicly available on the Web, including social security numbers, credit card numbers, trade secrets, and federally classified documents. Google Hacking for Penetration Testers, Third Edition, shows you how security professionals and system administratord manipulate Google to find this sensitive information and "self-police" their own organizations. You see how bad guys can manipulate Google to create super worms, and see how they can "mash up" Google with Facebook, LinkedIn, and more for passive reconnaissance. This third edition includes completely updated content and all new hacks such as Google scripting and using Google hacking with other search engines and APIs. Noted author Johnny Long, founder of Hackers for Charity, gives you all the tools you need to conduct the ultimate open source reconnaissance and penetration testing."--Page 4 of cover.
Google Search Basics -- Advanced Operators -- Google Hacking Basics -- Document Grinding and Database Digging -- Google's Part in an Information Collection Framework -- Locating Exploits and Finding Targets -- Ten Simple Security Searches That Work -- Tracking Down Web Servers, Login Portals, and Network Hardware -- Usernames, Passwords, and Secret Stuff, Oh My! -- Hacking Google Services -- Hacking Google Showcase -- Protecting Yourself from Google Hackers.
Includes index.
Vendor-supplied metadata.
Keywords: Google; Google; Web search engines; Computer security; Internet programming; Internet -- Security measures; Computer networks -- Security measures; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; Computer networks -- Security measures; Computer security; Internet programming; Internet -- Security measures; Web search engines; Electronic books